EFFORTS TO IMPROVE THE QUALITY OF SERVICE IN BIRTH MAKING CERTIFICATES AT POPULATION AND CIVIL REGISTRY OFFICE IN NAGEKEO REGENCY NTT - Frederikus Antonius Mana; Syahruddin Syahruddin; Muhammad Novan Prasetya (Nusantara Hasana Berdikari, 2022)
One of the functions of the Department of Population and Civil Registry is providing services to issue birth certificate. Unfortunately, in the Nagekeo Regency, among 164.431 of total population inhabitants only, 19.71% have birth certificate. In addition, the number of birth certificates issued in a year are not comparable with the number of applicants who submitted. This is caused by less information in the society about procedure and the importance of birth certificates. This study attempts to answer why the quality of these services is still low and what actors that actually affect it. This study used a qualitative method with descriptive approach which the data is collected through interviews, observation and documentation techniques. The result shows that there is low quality of service in making a birth certificate at the Department of Population and Civil Registration Nagekeo Regency. It happened because of there are no dimensions of tangibles, reliability, responsiveness, assurance, and empathy in the ministry. Emergency service offices still, ministry means minimal, there is no information about the procedures, as well as any element of discrimination in the ministry. The low quality of these services for structures, systems, services, human resources, facilities and services are inadequate. Also found the influence of factors of leadership and implementation of cultural elements one against the figure of a